Development of Conceptual Design of Automotive Bumper Beam at the Conceptual Design Stage - Hambali, A; Sapuan, S.M; Tajul, A.A; Taufik, S (Penerbit UTeM, 2011)
Development of a given engineering automotive component is a crucial process. Determining various factors that influence the development process of product is very important. This paper presents the development of automotive bumper beam at the conceptual design stage. The total design approach was employed to generate and design the conceptual design of automotive bumper beam. Analytical hierarchy process (AHP) was used to assist designers in determining the most appropriate decisions at the conceptual design stage. The paper reveals that the design concept 6 (DC-6) with a weight of 0.191 (19.1%) is the most appropriate decision during the development process at the conceptual design stage.